Study on the mechanical properties and pore structure of desert sand concrete (DSC) after high temperature - Liu, Haifeng; Li, Luoyin; Tao, Renguang; Che, Jialing; Zhu, Licheng; Sun, Shuai; Doh, Shu Ing (Elsevier Ltd, 2022)
To study the mechanical properties and pore structure of desert sand concrete (DSC), the ultrasonic testing, mechanical properties and mercury intrusion experiments of DSC after high temperature were carried out with different temperatures and desert sand replacement rate (DSRR). The ultrasonic wave velocity, mechanical properties and pore structure parameters after high temperature were measured. The mechanical properties degradation model was established. The relationship between the mechanical properties of DSC after high temperature and pore structure parameters was discussed. The results showed that the relative compressive strength, flexural strength and splitting tensile strength of DSC decreased gradually with temperature and arrived at the maximum with DSRR of 40%. The specific pore volume, average pore diameter, porosity ratio and threshold diameter of DSC after various temperatures were positively correlated with temperature. The porosity volume percentage of DSC with the diameter less than 100 nm decreased with temperature. However, the porosity volume percentage with the diameter ranging from 100 nm to 1000 nm increased with temperature. The porosity volume percentage of DSC with the diameter larger than 1000 nm had no significant change with temperature.